Business Capability and Creativepreneurship Readiness Predicting In-novative Business Model Quality in Semarang MSMEs - Albertus Setyo Sumargo; Ahmad Hafiyyan Shibghatalloh; Swanny Trikajanti Widyaatmadja (Jurnal Publikasi Ilmu Manajemen, 2026)
Creative micro, small, and medium enterprises (MSMEs) often recognize the value of innovation yet struggle to translate creative ideas into coherent business models because execution requires capabilities beyond creativity itself. This study examines whether perception of creativepreneurship and basic business capability predict creativepreneurship readiness, and whether readiness predicts innovative business model quality among creative and potentially creative MSMEs in Semarang, Indonesia. A cross-sectional survey yielded 102 responses; 78 complete cases met the prespecified eligibility criteria and were analyzed using PLS-SEM in SmartPLS 4 with 2,000 bootstrap subsamples. Basic business capability was strongly associated with readiness (β = 0.631, p < 0.001), while perception showed a smaller but positive directional association (β = 0.213, t = 1.907, one-tailed p = 0.028). Readiness strongly predicted innovative business model quality (β = 0.784, p < 0.001). The model explained 59.7% of readiness variance and 61.5% of business-model variance, with positive Q² values. The findings indicate that favorable perceptions are most useful when supported by practical routines in digital marketing, finance, operations, networking, storytelling, and business-model experimentation. Because the design is cross-sectional and some construct content overlaps, the coefficients are interpreted as predictive associations rather than causal effects.